2016
DOI: 10.3171/2015.4.spine14883
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive tubular microdiscectomy for recurrent lumbar disc herniation

Abstract: OBJECT The aim of the study was to investigate the safety and efficacy of minimally invasive tubular microdiscectomy for the treatment of recurrent lumbar disc herniation (LDH). As opposed to endoscopic techniques, namely microendoscopic and endoscopic transforaminal discectomy, this microscopically assisted technique has never been used for the treatment of recurrent LDH. METHODS Thirty consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Currently, PTED and MED are the most widely performed minimally invasive procedures in treating single-level LDH. MED is carried out based on traditional open surgery and microdiscectomy, and the surgical field is effectively enlarged with the use of a micro-endoscope, which minimizes damage to surrounding tissues [6,8]. PTED combines the endoscope and radiofrequency techniques and achieves direct extraction of the protruding disc by a working channel, which has the advantages of minimal invasiveness, less bleeding, easier anesthesia, and faster postoperative recovery [9,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, PTED and MED are the most widely performed minimally invasive procedures in treating single-level LDH. MED is carried out based on traditional open surgery and microdiscectomy, and the surgical field is effectively enlarged with the use of a micro-endoscope, which minimizes damage to surrounding tissues [6,8]. PTED combines the endoscope and radiofrequency techniques and achieves direct extraction of the protruding disc by a working channel, which has the advantages of minimal invasiveness, less bleeding, easier anesthesia, and faster postoperative recovery [9,32].…”
Section: Discussionmentioning
confidence: 99%
“…MED, first described by Foley et al in 1997 [7], uses a micro-endoscope for visualization and the paraspinous muscles are handled by muscle splitting through dilators, which causes less trauma to the muscle and soft tissue. Numerous studies have confirmed its safety and efficacy, even when treating recurrent LDH [6,8]. PTED, introduced by Yeung et al in 2002 [9], is more minimally invasive, with posterior column lumbar structures preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle injury can also be minimized by the use of minimally invasive muscle-sparing techniques [ 25 ], and selected minimally invasive procedures have also proven to be cost-effective in recently published cost-utility analysis [ 26 , 27 ]. Although the use of minimally invasive techniques has grown over the past few years, now becoming part of the surgeons' armamentarium for the treatment of numerous spinal conditions [ 28 33 ], the number of technical reports and publications focusing on the surgical challenges associated with minimally invasive muscle-sparing treatment of isthmic spondylolysis with symptomatic spondylolisthesis in adults is still limited [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While more technically demanding than traditional open discectomy, the use of tubular discectomy spread more widely after the adaptation of the instrumentation and technique to direct visualization utilizing an operative microscope. While clinical outcomes have been shown to be equivalent between open and tubular techniques, there are concerns regarding reherniation rates, as minimal removal of nuclear material is thought by some authors to contribute to post-discectomy reherniation and, ultimately, reoperation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%